Efficacy and Safety of Canagliflozin Compared to Sitagliptin and Glimepride as Add- on Therapy in T2DM - Yazan A. Bataineh (Journal of Global Pharma Technology, 2016)
Diabetes type II is a progressive disease and associated with many complications. Metformin is the first-line pharmacological therapy for type II. However, there is a second anti-diabetic drug can be added for patients who do not achieve sufficient glycemic control with metformin. In this study, we assess the efficacy and safety of newly approved anti-diabetic drugs Canagliflozin compared to Sitagliptin and Glimepiride patient with type II diabetes. Basically, 210 diabetic patients have received Canagliflozin 300 mg or Sitagliptin 100 mg or Glimepiride 4 mg for at least 16 weeks. Previously, the patient's glycemic state was uncontrolled by Metformin monotherapy. Glycated hemoglobin and Fasting blood glucose changes were used as an efficacy assessment from the baseline after metformin discontinuation. The safety profile was determined by comparing patient’s lipid profile, renal function, BUN, renal function and uric acid. Our results had shown a significant reduction in HBA1c and FBS in the three groups after 4 months of treatment (p <0.05). However, there was no significant change in the reducing effect between the three drugs (p= 0.704, 0.521). Canagliflozin and Glimepiride produce more reduction in triglycerides than Sitagliptin through the treatment period, although it is not significant, the change in the effect was significantly higher in Canagliflozin and Glimepiride comparing to Sitagliptin. Unlike Canagliflozin, Glimepiride and Sitagliptin produce a significant reduction in LDL after 4 months of treatment (p = 0.0318, 0.047) and significant difference in the effect (p = 0.042). Canagliflozin cause a significant elevation in LDL after the initiation of therapy (p= 0.034). The effect of Canagliflozin was significantly higher on HDL comparing to Glimepiride and Sitagliptin throughout the treatment (p = 0.048) and as a difference in the effect (p =0.043). Canagliflozin and Glimepiride produce a significant elevation in BUN comparing to Sitagliptin (p = 0. 004, 003), whereas, Canagliflozin and Sitagliptin produce a higher reduction in GFR than Glimepiride. Glimepiride is significantly elevates serum uric acid comparing to Canagliflozin and Sitagliptin with p= 0.0406. Conclusion: Canagliflozin, Sitagliptin, and Glimepiride are effective add-on therapy with metformin for proper control of blood glucose in T2DM. Canagliflozin and Glimepiride improve TGs and LDL greater than Sitagliptin. Sitagliptin produces less elevation in BUN than Canagliflozin and Glimepiride. Canagliflozin and Sitagliptin required renal monitoring throughout treatment.